Integrating Green Sports Infrastructure and Biopsychosocial Interventions: Sino-Nigerian Framework for Youth Engagement and Environmental Resilience in the Niger Delta - Ochor Daniel Chinonso (Indonesian Journal of Sport, Health and Physical Education Science, 2026)
Background: Speed and flexibility are important physical components that influence performance in basketball. Training methods such as plyometric training and mobility exercises are commonly used to enhance these abilities. However, the effectiveness of these training methods among collegiate male basketball players requires further investigation. Methods: This study employed a randomized group experimental design involving 45 male basketball players aged 18–25 years from JAIN University. The participants were divided into three groups: plyometric training group, mobility exercise group, and control group, with 15 subjects in each group. The experimental groups underwent their respective training programs for eight weeks, while the control group did not receive any specific training. Speed and flexibility were measured using the 50-meter run test and sit-and-reach test, respectively. Data were analyzed using Analysis of Covariance (ANCOVA) and Scheffé’s post-hoc test at a 0.05 level of significance. Result: The results showed significant improvements in speed and flexibility among the experimental groups compared to the control group. The mobility exercise group demonstrated better improvement in speed, while both plyometric and mobility training significantly enhanced flexibility. The obtained F-ratios for post-test and adjusted post-test scores were found to be statistically significant. Conclusion: It can be concluded that both plyometric training and mobility exercises are effective in improving speed and flexibility among collegiate male basketball players. Mobility exercises showed relatively greater improvement in speed, while both training methods were effective in enhancing flexibility.